Job preferences among clinical officers in public sector facilities in rural Kenya: a discrete choice experiment. Issue 1 (December 2016) - Takemura, Toshio; Kielmann, Karina; Blaauw, Duane
Abstract Background Clinical officers (COs), a mid-level cadre of health worker, are the backbone of healthcare provision in rural Kenya. However, the vacancy rate for COs in rural primary healthcare facilities is high. Little is known about factors motivating COs' preferences for rural postings. Methods A discrete choice experiment (DCE) questionnaire was used with 57 COs at public health facilities in nine districts of Nyanza Province, Kenya. The questionnaire was developed on the basis of formative qualitative interviews with COs (n  = 5) and examined how five selected job attributes influenced COs' preferences for working in rural areas. Conditional logit models were employed to examine the relative importance of different job attributes. Results Analysis of the qualitative data revealed five important job attributes influencing COs' preferences: quality of the facility, educational opportunities, housing, monthly salary and promotion. Analysis of the DCE indicated that a 1-year guaranteed study leave after 3 years of service would have the greatest impact on retention, followed by good quality health facility infrastructure and equipment and a 30% salary increase. Sub-group analysis shows that younger COs demonstrated a significantly stronger preference for study leave than older COs. Female COs placed significantly higher value on promotion than male COs. Conclusions Although both financial incentives and non-financial incentives were effective in motivating COs to stay in post, the study leave intervention was shown to have the strongest impact on COs' retention in our study. Further research is required to examine appropriate interventions at each career stage that might boost COs' professional identity and status but without leading to larger deficits in the availability of generalist COs.